The effectiveness of outdoor education on positive youth development and 21st century skills - Bakar, Ryan Abu; Fitri, Mustika; Hidayat, Yusuf; Ma'mun, Amung; Lardika, Rola Angga (UIR Press, 2024)
Background Problems: Adolescents face various social challenges, such as the need to succeed in a competitive environment, cope with stress, face a global pandemic, and must develop in the future as adults. Research Objectives: The purpose of this research is to create an outdoor program integrated with PYD and 21st century skills that form a generation of young people who are resilient and ready to face global challenges. Methods: The method used in this study was the quasi-experimental design research method. The design used in this study was Pretest-Posttest Control Group Design With More Than One Experimental Group. The research instrument to measure 21st century skills is the 21st century skills questionnaire, and to measure positive youth development (PYD) using the PYD 7Cs questionnaire. Findings and Results: There was a significant difference in the effect of the outdoor education program of PYD integration with the control group with a calculated f value of 17,993 and a sig value of 0.000. Similarly, there are differences between the 21st century skill integration group and the control group with a calculated f value of 15.579 and a sig value of 0.000. Conclusion: The results show that outdoor education that integrates PYD and 21st century skills has a better impact so that youth have excess energy if not channelled into positive activities. Youth needs in outdoor education activities are still an attractive choice. In the 21st century, outdoor education activities become meaningful learning with the condition that there is an integration concept both in 21st century skills and positive youth development.